1998
DOI: 10.1016/s0002-9440(10)65653-2
|View full text |Cite
|
Sign up to set email alerts
|

Typical and Atypical Carcinoid Tumors of the Lung Are Characterized by 11q Deletions as Detected by Comparative Genomic Hybridization

Abstract: Neuroendocrine tumors of the lung represent a wide spectrum of phenotypically distinct entities with different biological characteristics such as typical carcinoid tumor (TC), atypical carcinoid tumor (AC), large-cell neuroendocrine carcinoma (LCNEC), and small-cell lung carcinoma (SCLC). The histogenetic relationships between TC, AC, LCNEC, and SCLC are still unclear. This study was carried out to provide cytogenetic data about pulmonary neuroendocrine tumors and to evaluate their characteristic alterations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
2
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 42 publications
8
94
2
5
Order By: Relevance
“…3,13,14,32 Interestingly, a higher frequency of allelic loss of 18q was reported for classical midgut carcinoids 14,32 but not for lung carcinoid tumors. 13,27 In our study, the high frequency of loss of the entire chromosome 18 in ileal carcinoid tumors suggest that there are multiple tumor suppressor genes in chromosome 18 involving both the short and the long arms that play an important role in the tumorigenesis of ileal carcinoid tumors. Among the tumor suppressor genes harbored on chromosome 18q, the most extensively studied are the DCC gene localized at 18q21.2 and the DPC4 (Smad4) gene localized at 18q21.1.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…3,13,14,32 Interestingly, a higher frequency of allelic loss of 18q was reported for classical midgut carcinoids 14,32 but not for lung carcinoid tumors. 13,27 In our study, the high frequency of loss of the entire chromosome 18 in ileal carcinoid tumors suggest that there are multiple tumor suppressor genes in chromosome 18 involving both the short and the long arms that play an important role in the tumorigenesis of ileal carcinoid tumors. Among the tumor suppressor genes harbored on chromosome 18q, the most extensively studied are the DCC gene localized at 18q21.2 and the DPC4 (Smad4) gene localized at 18q21.1.…”
Section: Discussionmentioning
confidence: 56%
“…24 In previous reports, allelic loss of 11q was identified in pancreatic endocrine tumors, and ileal and lung carcinoid tumors but was not found in any appendiceal or rectal carcinoid tumors. 14,[25][26][27] Another study reported a high frequency of allelic loss at 11q13 locus (62%) in midgut carcinoid tumors, but a low frequency of succinate-ubiquinone oxireductase subunit D gene mutations, suggesting that other tumor suppressor genes may be targets for allelic loss at this region. 28 In our study, pancreatic endocrine tumors and carcinoid tumors demonstrated occasional loss of chromosome 16q with loss of loci at 16q11.2-q24.2.…”
Section: Discussionmentioning
confidence: 99%
“…pancreatic endocrine tumours and lung carcinoids. In the latter tumours, losses on chromosome 11, including the MEN1 locus, have been shown to be a primary tumour oncogenic event (Walch et al 1998, Zhao et al 2001. When comparing carcinoid tumours with an intact chromosome 18 and tumours with loss of chromosome 18, two distinct patterns of CNAs appeared.…”
Section: Discussionmentioning
confidence: 99%
“…3 The question of whether LCNEC should be considered as part of the NET spectrum remains unanswered. [15][16][17][18][19][20][21] Previous studies suggested several distinctive clinical features of LCNEC compared with well-differentiated NEC, including: tobacco use, male gender, advanced stage at presentation, and more frequent peripheral presentation. 10,11,13,[22][23][24] Historic LCNEC series have suggested a natural aggressive course with a median survival < 1 year.…”
Section: Discussionmentioning
confidence: 99%